PtRu catalysts supported on heteropolyacid and chitosan functionalized carbon nanotubes for methanol oxidation reaction of fuel cells - Cui, Z.; Li, C.; Jiang, San Ping (Royal Society of Chemistry, 2011)
A simple self-assembly approach has been developed to functionalize carbon nanotubes (CNTs) with chitosan (CS) and heteropolyacids (HPAs) of phosphomolybdic acid (H3PMo12O40, HPMo) and phosphotungstic acid (H3PW12O40, HPW). The non-covalent functionalization method, which introduces homogenous surface functional groups with no detrimental effect on graphene structures of CNTs, can be carried out at room temperature without the use of corrosive acids. The PtRu nanoparticles supported on HPAs-CS-CNTs have a uniform distribution and much smaller size as compared to those of the PtRu nanoparticles supported on conventional acid treated CNTs (PtRu/AO-CNTs). The onset and peak potentials for COad oxidation on PtRu/HPAs-CS-CNTs catalysts are more negative than those on PtRu/AO-CNTs, indicating that HPAs facilitate the electro-oxidation of CO. The PtRu/HPMo-CS-CNTs catalyst has a higher electrocatalytic activity for methanol oxidation and higher tolerance toward CO poisoning than PtRu/HPW-CS-CNTs. The better electrocatalytic enhancement of HPMo on the PtRu/HPAs-CS-CNTs catalyst is most likely related to the fact that molybdenum-containing HPAs such as HPMo have more labile terminal oxygen to provide additional active oxygen sites while accelerating the CO and methanol oxidation in a similar way to that of Ru in the PtRu binary alloy system.